عواضد لتقوية أحاديث الإمام مالك المنقطعة في كتابه الموطأ - حميداتو, مصطفى; بن مجدوب, إدريس (جامعة الوادي - University of Eloued, 2022)
يسلط هذا البحثُ الضوءَ على طرق تقوية العلماء لأحاديث الإمام مالك المنقطعة في الموطأ، ليستأنس بها الباحثون في تخريج أحاديثه وآثاره، خاصة الأحاديث التي تفرد بها. موضحا معنى الانقطاع، وكذا المعنى اللغوي والاصطلاحي للعاضد، ومسألة تقوية الأحاديث والخلاف فيها، كما يبين أسباب إيراد الإمام مالك للأحاديث المنقطعة بكثرة في الموطأ. فخلص الباحث إلى أنَّ الانقطاع في أحاديث الموطأ ليس كالانقطاع في غيره، وأنَّ من اقتصر على حديث الإمام مالك فقد كُفي تعبَ البحث والتفتيش، ووضع يدَه من ذلك على عروة وثقى لا تنفصم. the present research sheds light on Methods used by Muslim Scholars of Hadith to strengthen discontinued chain of narrators in hadiths reported by Imam Malik, so that these hadiths can be considered by researchers when studying his works, mainly reporting hadiths that were exclusively narrated by Imam Malik. The research also explains what is meant by discontinued chain of narrators and Adhid, or supporting hadith. It also examines the issue of strengthening hadiths, and scholars disgreement about it, and investigates why Imam Malik reported many discontinued-chain hadiths in his book Al-Muwatta. the researcher concludes that discontinued chain of narrators in hadiths reported by Imam Malik are Not like discontinued-chain hadiths reported by others, and that everyone relying on Imam Malik's hadiths will save the time and efforts of investigating their strength.
مقال
Keywords: الانقطاع؛ تقوية الأحاديث؛ العواضد؛ الموطأ